The Collateral Impact of COVID-19 Emergency on Neonatal Intensive Care Units and Family-Centered Care: Challenges and Opportunities - Cena, Loredana; Biban, Paolo; Janos, Jessica; Lavelli, Manuela; Langfus, Joshua; Tsai, Angelina; Youngstrom, Eric A.; Stefana, Alberto (Frontiers in Psychology, 2021)
During the Coronavirus disease 2019 (COVID-19) pandemic, people who visit neonatal intensive care units (NICUs) need special attention, and this need will continue even after the most intense part of the crisis has passed. Although COVID-19 has so far only affected newborn infants directly to a relatively limited extent, the effects of the disease reverberate through the physical, emotional, and psychological well-being of both new parents and NICU staff members and reduces parental and family visitation privileges. Such impacts can have indirect adverse consequences for children’s cognitive, emotional, and social development. In this article, based on empirical data from the literature, we provide reflections on the implications of the COVID-19 emergency for NICU systems and families as well as some indications for how to support both parents and NICU staff. This global health crisis is a tragedy. Nevertheless, it may also be an opportunity to strengthen NICU health care systems and services.